1994
DOI: 10.1021/np50107a016
|View full text |Cite
|
Sign up to set email alerts
|

SB-202742, a Novel β-Lactamase Inhibitor Isolated from Spondias mombin

Abstract: SB-202742 [1], an anacardic acid derivative possessing beta-lactamase inhibitory activity, has been isolated from a hexane extract of the plant, Spondias mombin. Its isolation, structure determination, and biological activity are reported herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 10 publications
0
32
0
2
Order By: Relevance
“…Preliminary reports suggest that the phenolic acid, 6-alkenyl-salicylic acid from Spondias mombin are responsible for the antibacterial and molluscicidal of this plant extract (Corthout et al, 1994). In another study, the anacardis acid derivative from the hexane extract of the plant was showed to possess beta lactamase inhibitory properties (Coates et al, 1994). Keshinro, 198524 Wound-healing Deferreyra, 1981, 1997Jaramillo and Ahnmadebormol, 1983;Ajao et al, 1985;Villegas et al, 1997 The plant extract has been shown to possess phenolic derivatives with antiherpes and antioxidant properties, which have been formulated for use in Brazil (Corthout et al, 1992;Caster et al, 1998;Shultes and Raffauf, 1990;Mats, 1994).…”
Section: Biological Activitiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Preliminary reports suggest that the phenolic acid, 6-alkenyl-salicylic acid from Spondias mombin are responsible for the antibacterial and molluscicidal of this plant extract (Corthout et al, 1994). In another study, the anacardis acid derivative from the hexane extract of the plant was showed to possess beta lactamase inhibitory properties (Coates et al, 1994). Keshinro, 198524 Wound-healing Deferreyra, 1981, 1997Jaramillo and Ahnmadebormol, 1983;Ajao et al, 1985;Villegas et al, 1997 The plant extract has been shown to possess phenolic derivatives with antiherpes and antioxidant properties, which have been formulated for use in Brazil (Corthout et al, 1992;Caster et al, 1998;Shultes and Raffauf, 1990;Mats, 1994).…”
Section: Biological Activitiesmentioning
confidence: 93%
“…There is evidence of arabinofuranose residues as structural features of the Spondias gums. Coates et al (1994) isolated a novel betalactamase inhibitor from Spondias mombin. Two caffeoyl esters: 2-0-caffeoyl-(+)-allohyroycritic acid and chlorogenic and butyl ester with antiviral properties were isolated by Corthout et al (1992).…”
Section: Phytochemistry Of Spondias Mombinmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary reports suggest that the phenolic acid, 6-alkenylsalicylic acid in the leaf extract of Spondias mombin are responsible for its antibacterial property 6 . In another study, the anacardis acid derivative from the hexane extract of the plant was showed to possess beta lactamase inhibitory properties 7 . The anti-malarial activity of Spondias mombin discovered lately is said to have been linked to a range of compounds like anthraquinones, berberine, flavonoids, naphthoquinones, sesquiterpenes, quassiniods, indole and quinoline alkaloids present in the leaves 8 .…”
Section: Introductionmentioning
confidence: 98%
“…Crude Spondias mombin (L. Anacardiaceae) leaves extracts have been reported to modulate multiple behaviours (novelty-induced, sedative, antipsychotic, antiepileptic) in mice and rats (Ayoka et al 2005). Previous studies have reported extraction of different chemical compounds (phenolic acid 6-alkenyl-salicylic acid, anarcardic acid and phenolic derivatives) from Spondias mombin, which exhibited different biological properties including antibacterial, molluscicidal, antiviral and antioxidant effects (Corthout et al, 1994;Coates et al, 1994;Castner et al, 1998).…”
Section: Introductionmentioning
confidence: 99%